An Evidence-Based Co-Design and Iterative Approach to Developing an Online Sexual Health Intervention for Older Chinese Women: A Qualitative Study Protocol - FuLi Wang; Yu Hu (International Journal of Qualitative Methods)
Sexual health is an essential component of overall well-being, yet it is a neglected aspect of health care for older women in China, where cultural stigmas and structural barriers limit access to sexual health communication and services. This study protocol describes the co-creative and iterative methodological framework used to develop an evidence-based online intervention tailored to the sexual health needs of Chinese older women. The research follows a multi-phase approach that begins with a systematic literature review to consolidate key intervention strategies and is followed by co-design and iterative focus group sessions involving older women, their family members, healthcare providers, and digital platform developers. A WeChat mini-application is proposed as the digital intervention platform that can incorporate interactive learning modules, anonymous peer-support forums, and culturally adapted content. The intervention framework is evaluated using qualitative research methods including thematic analysis of focus group discussions and iterative refinement through SMART principles. This study contributes to health communication and digital intervention research on social problems in the context of digital intellectual social development by providing a structured, user-centered approach that bridges the gap between theoretical knowledge and practical application. Findings from this research will inform the development of scalable, culturally sensitive digital interventions that address critical gaps in sexual health education and access.